Water and Nitrogen Management on Micronutrient Concentrations in Winter Wheat. (1st May 2014) - Wang, Shaoxia; Tian, Xiaohong; Li, Meng; Ni, Yijun; Li, Jin; Li, Hongyun; Wang, Shujuan; Chen, Yanlong; Guo, Chunhui; Zhao, Aiqing
Abstract : Water status and N fertility are the critical factors in micronutrient accumulation in grain of wheat ( Triticum aestivum L.). This field experiment was conducted to examine whether the changes in N fertility and water management can influence micronutrient concentration and bioavailability in wheat grown in soils with existing low micronutrient concentrations within drought‐prone regions. The results indicate that fertilizer N (120 or 240 kg N ha −1 ) application significantly improved grain Zn, Fe, Cu, and protein concentration with a mean increase of 24.7, 39.2, 18.6, 23.9% in 2009/2010 and 8.9, 21.1, 10.5, 29.6% in 2010/2011, respectively, when compared with the unfertilized treatment. However, grain Mn concentration in both cropping seasons were significantly decreased (on average by 8.4%) by N fertilization. Compared to the no irrigation treatment (NI), the water‐saving treatment (RF) significantly increased grain Zn by an average of 13.2%, grain Fe by 22.2%, grain Mn by 4.4%, and grain protein by 8.3%. Grain phytic acid (PA) concentration and PA/micronutrient ratios were on average 28.0 and 32.2% lower in the N fertilized treatment than in the unfertilized treatment. Decreasing the N application rate from 240 to 120 kg N ha −1 did not affect much of the grain nutritional quality, with the exception of a significant decrease in grain Zn concentration, and a significant increase in grain PA concentrations and the PA/Zn molar ratio. These data demonstrate the importance of monitoring grain Zn concentrations, and perhaps the inclusion of supplemental Zn when adopting alternative N fertilizer management regimes in northern China.